2021
DOI: 10.1097/sla.0000000000005065
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Opioid Exposure in Trauma: A Secondary Analysis of the Multimodal Analgesia Strategies for Trauma (MAST) Randomized Trial

Abstract: Objective: Evaluate the effect of age on opioid consumption after traumatic injury. Summary Background Data: Older trauma patients receive fewer opioids due to decreased metabolism and increased complications, but adequacy of pain control is unknown. We hypothesized that older trauma patients require fewer opioids to achieve adequate pain control. Methods: A secondary analysis of the multimodal analgesia str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…7,8,14 Burton et al 15 determined that multimodal pain management reduces the number of opioids used and the prescribed dose in patients with thoracic trauma. Similarly, Hatton et al 16 found that multimodal pain management applied in elderly patients decreased the number of opioids used and, thus, the complications. The most important reason is that the multiple analgesia met-hod is thought to provide effective analgesia because it affects both peripheral and central pain sources and causes fewer side effects at low doses.…”
Section: Discussionmentioning
confidence: 89%
“…7,8,14 Burton et al 15 determined that multimodal pain management reduces the number of opioids used and the prescribed dose in patients with thoracic trauma. Similarly, Hatton et al 16 found that multimodal pain management applied in elderly patients decreased the number of opioids used and, thus, the complications. The most important reason is that the multiple analgesia met-hod is thought to provide effective analgesia because it affects both peripheral and central pain sources and causes fewer side effects at low doses.…”
Section: Discussionmentioning
confidence: 89%
“…The multimodal analgesic approach (MMA) or "balanced analgesia" was introduced with the aim of decreasing the exposure to opioids, to address acute pain effectively, and enhance recovery after surgical procedure and trauma. It is defined as the integrated use of multiple strategies including systemic analgesics, regional analgesic techniques, and non-pharmacological interventions to affect peripheral and/or central nervous system sites in the pain pathway with the main aim of achieving a synergistic effect of the various classes of drugs used at lower analgesic doses [344][345][346][347][348][349]. MMA provides the use of: (1) analgesics, including opioids, nonopioid analgesics (such as acetaminophen and NSAIDs), the gabapentinoids (gabapentin and pregabalin), serotonin norepinephrine reuptake inhibitors, tricyclic antidepressants, and N-methyl-d-aspartate (NMDA) receptor antagonists; (2) neuraxial (epidural and intrathecal) analgesia; (3) peripheral nerve blocks; and (4) intraarticular and wound infiltration with local anaesthetics.…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%
“…The synergy created when multimodal regimens are used to target discrete components of the peripheral and central pain pathways leads to effective analgesia at lower opioid dosing, reducing related risk and producing fewer adverse effects [343,344,349] MMA should be individualized in a muldisciplinary approach according to the patient; type of pain; mechanism of pain (inflammatory or neuropathic); type of surgical procedure; location of pain; expected duration of pain. Because of their opioidsparing effects, multimodal strategies are useful and safe for elderly patients [345,346].…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%
See 1 more Smart Citation